Advances in the use of ECMO in oncology patient - Xiangnan Teng; Jiali Wu; Jing Liao; Shanling Xu (Cancer Medicine, 2023)
Abstract Background Over the past decade, ECMO has provided temporary cardiopulmonary support to an increasing number of patients, but the use of extracorporeal membrane oxygenation (ECMO) to provide temporary respiratory and circulatory support to adult patients with malignancy remains controversial. Objectives This paper reviews the specific use of extracorporeal membrane oxygenation (ECMO) in oncology patients. Methods We searched PubMed, CINAHL, Cochrane Library, and Embase databases for studies on the use of ECMO in cancer patients between 1998 and 2022. Twenty‐four retrospective, prospective, and case reports were included. The primary outcome was survival during extracorporeal membrane oxygenation. Results Most studies suggest that ECMO can be used in oncology patients requiring life support during surgery, solid tumor patients with respiratory failure, and hematological tumor patients requiring ECOM as a supportive means of chemotherapy; however, in patients with hematologic oncology undergoing hematopoietic stem cell transplantation, there was no clear benefit after the use of ECMO. Conclusion Current research suggests that ECMO may be considered as a salvage support in specific cancer patients. Future studies should include larger sample sizes than those already conducted, including studies on efficacy, adverse events, and health.